2018
DOI: 10.1073/pnas.1719907115
|View full text |Cite
|
Sign up to set email alerts
|

Three classes of recurrent DNA break clusters in brain progenitors identified by 3D proximity-based break joining assay

Abstract: We recently discovered 27 recurrent DNA double-strand break (DSB) clusters (RDCs) in mouse neural stem/progenitor cells (NSPCs). Most RDCs occurred across long, late-replicating RDC genes and were found only after mild inhibition of DNA replication. RDC genes share intriguing characteristics, including encoding surface proteins that organize brain architecture and neuronal junctions, and are genetically implicated in neuropsychiatric disorders and/or cancers. RDC identification relies on high-throughput genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
94
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(107 citation statements)
references
References 32 publications
7
94
0
Order By: Relevance
“…To extend these studies, we exploited our finding that joining of two DSBs occurs more frequently if they lie on the same cis chromosome (12,13). Thus, we introduced DSBs into each of the 20 mouse chromosomes as baits for HTGTS libraries from control or APH-treated NSPCs (14). This analysis confirmed previously identified RDCs and identified many more.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…To extend these studies, we exploited our finding that joining of two DSBs occurs more frequently if they lie on the same cis chromosome (12,13). Thus, we introduced DSBs into each of the 20 mouse chromosomes as baits for HTGTS libraries from control or APH-treated NSPCs (14). This analysis confirmed previously identified RDCs and identified many more.…”
Section: Introductionsupporting
confidence: 56%
“…Based on identification frequency with different baits and RDC-DSB density, we ranked relative RDC-gene robustness. On this basis, 19 originally identified plus 11 newly identified RDC-genes were highly robust (14). Of note, four of these highly robust RDC-genes were identifiable in untreated controls, but became more robust with APH-treatment, consistent with ectopic replication stress augmenting an ongoing endogenous process (11,14).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Strikingly, single‐cell sequencing of human frontal cortex neurons has revealed that up to 41% of them had at least one very large (in the order of the Mb) de novo copy number variation (CNV), most of them being deletions . CNVs have also been detected at high frequency in mouse neural stem/progenitor cells, many of them in large genes . The inherent susceptibility to genomic instability of genes coding physiologically important proteins is difficult to understand from an evolutionary point of view.…”
Section: The Evolution Point Of Viewmentioning
confidence: 99%
“…94 CNVs have also been detected at high frequency in mouse neural stem/progenitor cells, many of them in large genes. 13,95 The inherent susceptibility to genomic instability of genes coding physiologically important proteins is difficult to understand from an evolutionary point of view. However, pathologic somatic mutations have been described in healthy individuals at subclinical frequencies, indicating that brain function may cope with mutated clone, depending on their size.…”
Section: The Evolution Point Of Viewmentioning
confidence: 99%